The impact of NHS charging regulations on healthcare access and utilisation among migrants in England: a systematic review - Nazanin Rassa; Margaret McCarthy; Seb Casalotti; Claire Zhang; Fatima Wurie; Colin Brown; Ines Campos-Matos (BMC, 2023)
Abstract Background The NHS Charges to Overseas Visitors Regulations 2015 outline when healthcare costs should be recuperated from overseas visitors in England. National and global stakeholders have expressed concerns that charging may exacerbate health inequalities and undermine public health efforts especially among vulnerable migrant groups. This review aims to systematically describe the evidence regarding the impact of NHS charging regulations on healthcare access and utilisation and health outcomes for migrants in England. Methods A systematic search of scientific databases and grey literature sources was performed. Quantitative and qualitative studies, case studies and grey literature published between 1 January 2014 and 1 April 2021 were included. Screening, data extraction and quality appraisal were carried out in accordance with PRISMA guidelines. Results From the 1,459 identified studies, 10 were selected for inclusion. 6 were qualitative, 3 were mixed methods and 1 was quantitative. The evidence is lacking but suggests that fears of charging and data sharing can deter some migrants from accessing healthcare. There is also evidence to suggest a lack of knowledge of the charging regulations among patients and healthcare professionals is contributing to this deterrence. Conclusions Further independent research supported by strengthening of data collection is required to better understand the effects of charging on healthcare and health outcomes among vulnerable migrants. Our findings support improved training and communication about NHS Charging Regulations for patients and professionals.